Laser therapy in the rehabilitation of orofacial diseases in Pediatric Dentistry (Research, Society and Development, 2024)
Introduction: Laser, the amplification of light by stimulated emission of radiation, originated from the abbreviation Light Amplification by Stimulated Emission of Radiation, which in Brazilian Portuguese means Luz Amplificada pela Emissão Estimulada de Radiação. The laser has specific characteristics, such as the amount of energy and wavelengths suitable for penetrating tissues and exerting an effective influence on the synthesis, release, and metabolism of various substances involved in analgesia. Objective: To evaluate the efficacy and benefits of low-intensity laser therapy in the rehabilitation of orofacial diseases in pediatric dental patients, considering its analgesic, anti-inflammatory, and biostimulatory effects. Methodology: This was an integrative review, with a qualitative, descriptive-exploratory approach, highlighted by an integrative, systematic, and qualified analysis developed through research in online databases, BIREME and PUBMED, using pre-selected keywords, resulting in indexed research from the period 2020 to 2024. Results: gather the main findings in the literature on the topic. The discussion compares the results obtained in this integrative review with the results of other authors on the same subject. Conclusion: The positive experience provided by laser therapy tends to increase the confidence and collaboration of young patients during procedures, making treatment more efficient and improving the child's relationship with the dental environment. This represents a significant advancement in terms of comfort and treatment adherence in pediatric dentistry.